Genomic Selection Module 6.0b: Basic genomic selection and the training population Part 2 - Sneller, C. (International Livestock Research Institute, 2017)
Part 6b in a series of eight training modules on Genomic Selection. The modules are prepared by the Clay Sneller, lead plant breeder at the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI Hub), in Nairobi